A qualitative investigation into the meaning of work: Some preliminary findings on NGOs in Southern Thailand - Wesarat, Phathara-on; Sharif, Mohmad Yazam; Abdul Majid, Abdul Halim (2008)
The objective of this paper is to share some preliminary findings on what work means to non-governmental organization (NGO) officers in Thailand. Non-Governmental Organizations (NGOs) play important roles both at the international level and national level in any country. In Thailand, NGOs operate on various issues such as labor rights, support for children, health promotion and consumers’ rights protection. These NGOs are also known as non-profit organizations. Their activities are meant to support and protect public interest and are not for monetary gain or commercial purposes. This study is part of a doctoral research using the qualitative approach. In our preliminary findings, we found that generally the NGOs’ workers in southern Thailand are educated people. The research question posed is: why are these people working in NGOs? They are well qualified to work even in firms (and probably earn better pay) but they chose to work in NGOs. Thus, this paper aims to examine what motivates them to work with NGOs. Most researches found in the organizational literature have focused on work motivation in the public and private organizations, while work motivation in NGOs has somewhat been neglected. Based on previous studies, there were already factors which affected employee work motivation which had been identified. Some motivational factors (from studies such as Maslow and Herzberg) were used to develop a guiding research framework for our qualitative investigation. This study had used a mixed approach (also referred to as a triangulation method) within a qualitative study comprising in-depth interviews, non-participant observation, and secondary documents. The respondents in this study were the NGOs’ workers in Southern Thailand selected from two organizations: 1) the Consumers Rights Protection Project group, 2) the Promotion of Quality of Work Life for Informal Sector (Production Scheme). The preliminary findings on the workers’ work processes or what they had been doing in NGOs they work for are discussed in the paper. Work motivators in this study were used as a basis for discussing the meaning of work to the officers who work in the NGOs. The meaning of work to people who work in NGOs is hypothesized to be different than those who work in other types of organizations such as firms and governmental agencies. Pay and job security could be not that important to NGO’s managers and officers.